A nature-based solution selection framework: Criteria and processes for addressing hydro-meteorological hazards at open-air laboratories across Europe. (1st April 2023) - Gonzalez-Ollauri, Alejandro; Mickovski, Slobodan B.; Anderson, Carl C.; Debele, Sisay; Emmanuel, Rohinton; Kumar, Prashant; Loupis, Michael; Ommer, Joy; Pfeiffer, Jan; Panga, Depy; Pilla, Francesco; Sannigrahi, Srikanta; et al.
Abstract: Nature-based solutions (NbS) can be beneficial to help human communities build resilience to climate change by managing and mitigating related hydro-meteorological hazards (HMHs). Substantial research has been carried out in the past on the detection and assessment of HMHs and their derived risks. Yet, knowledge on the performance and functioning of NbS to address these hazards is severely lacking. The latter is exacerbated by the lack of practical and viable approaches that would help identify and select NbS for specific problems. The EU-funded OPERANDUM project established seven Open-Air Laboratories (OALs) across Europe to co-develop, test, and generate an evidence base from innovative NbS deployed to address HMHs such as flooding, droughts, landslides, erosion, and eutrophication. Herein, we detail the original approaches that each OAL followed in the process of identifying and selecting NbS for specific hazards with the aim of proposing a novel, generic framework for selecting NbS. We found that the process of selecting NBS was overall complex and context-specific in all the OALs, and it comprised 26 steps distributed across three stages: (i) Problem recognition, (ii) NbS identification, and (iii) NbS selection. We also identified over 20 selection criteria which, in most cases, were shared across OALs and were chiefly related to sustainability aspects. All the identified NbS were related to the regulation of the water cycle, and they were mostly chosen according to three main factors: (i) hazard type, (ii) hazard scale, and (iii) OAL size. We noticed that OALs exposed to landslides and erosion selected NbS capable to manage water budgets within the soil compartment at the local or landscape scale, while OALs exposed to floods, droughts, and eutrophication selected approaches to managing water transport and storage at the catchment scale. We successfully portrayed a synthesis of the stages and steps followed in the OALs' NbS selection process in a framework. The framework, which reflects the experiences of the stakeholders involved, is inclusive and integrated, and it can serve as a basis to inform NbS selection processes whilst facilitating the organisation of diverse stakeholders working towards finding solutions to natural hazards. We animate the future development of the proposed framework by integrating financial viability steps. We also encourage studies looking into the implementation of the proposed framework through quantitative approaches integrating multi-criteria analyses. Graphical abstract: Image 1 Highlights: We present a novel NbS selection framework based on 6 real case studies. The case studies strived to address hydro-meteorological hazards across Europe. The framework has 26 steps distributed across 3 stages. We identified 20 NbS selection criteria chiefly related to sustainability issues. All the selected NbS were related to the regulation of the water cycle.